RANCANG BANGUN SISTEM INVENTORY PENGENDALIAN PERSEDIAAN DENGAN MENGGUNAKAN METODE LOT SIZING ”LOT FOR LOT” BERBASIS WEBSITE DI ZULFAHCOLLECTION.ID - Ainun Rofiq Marhendra; Sidqon, S.Si., M.Si, Mochamad (Jurnal Rekayasa Sistem Informasi dan Teknologi, 2024)
This abstract describes the design and implementation of an inventory control system using the "Lot for Lot" lot sizing method at ZulfahCollection.id, a small and medium-sized enterprise (SME), utilizing the Laravel framework. The primary objective of this research is to enhance operational efficiency and optimize inventory management according to the business needs. The process began with an in-depth needs analysis to understand the operational processes and inventory requirements of the SME, which then served as the foundation for designing the inventory control system. The design focused on key aspects such as data security, an intuitive user interface, efficient warehouse workflow, and the implementation of the "Lot for Lot" lot sizing method. Following the design phase, the system was developed as a web application using the Laravel framework and thoroughly tested to ensure its quality and performance. The testing included functionality, performance, and data security to ensure the system's reliability in daily operations. Intensive training was provided to the SME users to ensure a comprehensive understanding of the system and the applied lot sizing method. An evaluation was conducted to assess the system's effectiveness in managing inventory and reducing warehouse costs. The results indicated that the system successfully helped ZulfahCollection.id enhance operational efficiency and optimize their inventory management. This research not only benefits ZulfahCollection.id but also offers valuable insights for other SMEs looking to improve their inventory management through web-based technology. It is hoped that this research can make a significant contribution to the field of inventory management and information technology for SMEs, assisting them in achieving better operational efficiency and significant cost reductions.